Correlation Between Hematocrit Levels and Length of Stay among Dengue Infection Patients at Wangaya General Hospital - Nyoman Adi Wirasatya Wibawa; Saraswati Laksmi Dewi; Putu Arya Giri Prebawa; Dewa Ayu Alit Suka Astini (International Journal of Biomedical Science and Travel Medicine, 2026)
Dengue infections, such as Dengue Fever (DF) and Dengue Hemorrhagic Fever (DHF), remain significant public health issues in Indonesia, including Bali Province. The high incidence and mortality rates due to DHF have substantial impacts, particularly concerning treatment costs and length of hospitalization. This study aims to analyze the correlation between hematocrit levels and hospital length of stay among DHF patients at RSUD Wangaya in 2023. The variable studied was hematocrit levels. This research employed an analytical observational method with a retrospective cross-sectional design, using medical record data from DHF patients at RSUD Wangaya from January 1, 2023, to December 31, 2023. Data analysis was conducted using Pearson's correlation test to assess the relationship between hematocrit levels and hospital length of stay. The study results showed that the majority of patients were male (58.3%) and that most were under 50 years old (66.7%). The most common clinical manifestation was fever (98.1%), and most patients had platelet counts below 100,000/µL (77.8%). The average hematocrit was 40.6% in the group with levels <50% and 52.1% in the group with levels ?50%. Bivariate analysis using Spearman's correlation test showed no significant association between hematocrit levels and hospital length of stay among dengue patients (p = 0.835). This study concludes that although hematocrit levels are critical clinical indicators in DHF patients, no significant correlation was found between hematocrit levels and hospital length of stay.